Sodium channel SCN8A (Nav1.6): properties and de novo mutations in epileptic encephalopathy and intellectual disability - O'Brien, Janelle E.; Meisler, Miriam H. (Frontiers in Genetics, 2013)
The sodium channel Nav1.6, encoded by the gene SCN8A, is one of the major voltage-gated channels in human brain. The sequences of sodium channels have been highly conserved during evolution, and minor changes in biophysical properties can have a major impact in vivo. Insight into the role of Nav1.6 has come from analysis of spontaneous and induced mutations of mouse Scn8a during the past 18 years. Only within the past year has the role of SCN8A in human disease become apparent from whole exome and genome sequences of patients with sporadic disease. Unique features of Nav1.6 include its contribution to persistent current, resurgent current, repetitive neuronal firing, and subcellular localization at the axon initial segment and nodes of Ranvier. Loss of Nav1.6 activity results in reduced neuronal excitability, while gain-of-function mutations can increase neuronal excitability. Mouse Scn8a (med) mutants exhibit movement disorders including ataxia, tremor and dystonia. Thus far, more than ten human de novo mutations have been identified in patients with two types of disorders, epileptic encephalopathy and intellectual disability. We review these human mutations as well as the unique features of Nav1.6 that contribute to its role in determining neuronal excitability in vivo. A supplemental figure illustrating the positions of amino acid residues within the 4 domains and 24 transmembrane segments of Nav1.6 is provided to facilitate the location of novel mutations within the channel protein.